2006
DOI: 10.3892/ijo.29.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Human DEAD-box/RNA unwindase rck/p54 contributes to maintenance of cell growth by affecting cell cycle in cultured cells

Abstract: Abstract. Understanding the control of gene expression in cancer cells requires defining the molecular and cellular basis of RNA metabolism compared with that in steady-state normal cells. Previously, we reported evidence that human RNA structure-modifying unwindase rck/p54, a member of the DEAD-box family, was highly expressed in most of the malignant cell lines tested and that this expression was linked to malignant transformation. Here, we show that rck/p54 positively affects cell growth, probably by modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…The overexpression of RCK/p54 gene has been found in many malignancies, such as colorectal cancer, cervical carcinoma, hepatocarcinoma. 5,13,14 In this study, we want to explore whether RCK/p54 plays a role in maintaining the malignant phenotypes and becomes a therapeutic target for the treatment of human colorectal cancers. RNA interference (RNAi) is a recently discovered posttranscriptional gene silencing mechanism, which can specifically silence gene therapy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overexpression of RCK/p54 gene has been found in many malignancies, such as colorectal cancer, cervical carcinoma, hepatocarcinoma. 5,13,14 In this study, we want to explore whether RCK/p54 plays a role in maintaining the malignant phenotypes and becomes a therapeutic target for the treatment of human colorectal cancers. RNA interference (RNAi) is a recently discovered posttranscriptional gene silencing mechanism, which can specifically silence gene therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Our results were also consistent with Akao Y's research in human cervical carcinoma cells. 13 Apoptosis induction by RCK/p54-shRNA1 in LoVo cells. To determine whether the proliferation inhibition of LoVo cells by RCK/p54shRNA1 was induced by cell apoptosis, we performed FCM and TUNEL assays to measure the levels of apoptosis in LoVo cells expressing RCK/p54shRNA.…”
Section: Resultsmentioning
confidence: 99%
“…Can both promote and repress translation initiation: associates with P-bodies, ATP hydrolysis allows release from P-bodies and translation initation [32][33][34][35][36][37] 58,65 Developmental roles in many species [57][58][59][60][61][62] Overexpression in several cancers [53][54][55][56] Stimulation of cell cycle progression and proliferation [70][71][72][73][74] Cell cycle progression/proliferation Dhh1p important for recovery from DNA damageinduced G1/S cell cycle arrest in yeast DDX6 required for S-phase progression and cell viability in HeLa and LoVo cells, 73,74 and proliferation in xenograft models 74 (siRNA studies)…”
Section: Translationmentioning
confidence: 99%
“…Several studies, with both the human DDX6 and the yeast Dhh1p, have indicated that this protein acts as a positive regulator of cell cycle progression: Dhh1p has been shown to be important for recovery from DNA-damage-dependent G1/S cell cycle arrest, 72 while two separate studies demonstrated that siRNA knockdown of DDX6 resulted in S-phase cell cycle arrest. 73,74 Furthermore, these studies showed that siRNA knockdown of DDX6 resulted in a reduction in cell viability, 73 as well as an increase in cell apoptosis and a reduction in their ability to form tumors in xenograft models. 74 Additionally, overexpression of DDX6 was shown to increase expression of the oncogene c-Myc, consistent with the idea that it would have a positive effect on cell proliferation.…”
mentioning
confidence: 99%
“…A second mechanism by which CNOT7 and CNOT8 contribute to cell proliferation may be by positively regulating the expression of genes required for cell proliferation, such as the DEAD-box RNA helicase DDX6/Rck/p54 (Akao et al, 2006). Interestingly, DDX6 is a homologue of yeast Dhh1, which interacts with the Ccr4 -Not complex (Coller et al, 2001;Maillet and Collart, 2002).…”
Section: Cnot7 and Cnot8 Are Important For Efficient Cell Proliferatimentioning
confidence: 99%